Pathophysiologie des Lymphödems – 2012 - Olszewski, W. L. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2012)
Lymphedema of the limbs has become a frequent pathological condition after soft tissue inflammation, trauma, removal of lymph nodes in cancer and long-lasting ulcerations. Lymphatics draining the diseased tissues become occluded. Microsurgery helps in the formation of anastomoses and collaterals bypassing the obstruction site. Surgeons operating on the lymphatics should be aware of the tissue fluid/lymph formation mechanism, hydraulics of tissue fluid/lymph, tissue metabolism and waste material utilization, immune function in terms of elimination of microbial and tumor antigens and raising tolerance to own tissue antigens of injured tissues necessary for wound healing as well as classification of diseases of lymphatics. In this review we present the actual definition of the lymphatic system, how it is changed in lymphedema, and, in particular, tissue fluid/lymph biochemistry, pressure and flow, histopathology and tissue fluid location, and finally how to manage the most common complication dermato-lymphangioadenitis. Detailed knowledge of the anatomy of upper limb limphaties should prevent their damage and loss of function.
Keywords: lymphedema; lymphatics; lymph nodes; lymph; tissue fluid